2019
DOI: 10.1590/1806-9282.65.6.755
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil-induced agranulocytosis as a rare complication of antithyroid drugs in a patient with Graves’ disease

Abstract: SUMMARY INTRODUCTION: Graves’ disease (GD) is an autoimmune disorder characterized by hyperthyroidism. Antithyroid drugs (ATDs) are available as therapy. Agranulocytosis is a rare but potentially fatal complication of this therapy. In this study, we report agranulocytosis induced by propylthiouracil (PTU) in a patient with GD and the difficulties of clinical management. CASE: RNBA, male, 30 years old, with GD, treated with propylthiouracil (PTU). He progressed with pharyngotonsillitis. Then, PTU was suspende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Majority of the agranulocytosis cases reported in 90 days after the commence of therapy. The patients should receive instruction from physicians and report if any symptoms observed such as pancytopeniatemperature, sore throat/pharyngitis, diarrhea [16]. In recent study the potentially fatal side effects agranulocytosis was reported in 2.7% of patients and fever (80%), and sore throat (82%) was reported within 3 months after onset of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the agranulocytosis cases reported in 90 days after the commence of therapy. The patients should receive instruction from physicians and report if any symptoms observed such as pancytopeniatemperature, sore throat/pharyngitis, diarrhea [16]. In recent study the potentially fatal side effects agranulocytosis was reported in 2.7% of patients and fever (80%), and sore throat (82%) was reported within 3 months after onset of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They include pruritus, skin rashes, agranulocytosis, hepatic injury, aplastic anemia, and so on. [ 6 8 ] In addition, we noticed that some patients with GD treated with oral ATDs manifested symptom of myalgia. CK is a muscle-specific kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Oral ATDs’ common side effects include: rash, pruritus, liver damage, and leukopenia. [ 6 , 7 ] But there are some other rare adverse reactions, such as aplastic anemia, [ 8 ] increased serum creatine kinase (CK) that are easily ignored. We noticed that some GD patients with oral ATDs manifested myalgia and increased serum CK concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Pancytopenia was found in 1.2% of patients with agranulocytosis due to antithyroid drugs. Hemopoetic damage can be found in patients without any clinical manifestations, so it is necessary to consider a complete count examination after 2 weeks of taking anti-thyroid drugs (6,12,14,15).…”
Section: Clinical Manifestationsmentioning
confidence: 99%